Analysis of the Cultural Dimensions of Indonesian People on Purchase Decisions: A Case Study of Karen's Diner Restaurant in Indonesia - Atikah Amaliadanti; Niken Febrina Ernungtyas; Lukita Wijaya (Jurnal Indonesia Sosial Teknologi, 2024)
This study uses a constructivist paradigm and a qualitative approach to analyse six elements of Hofstede's Cultural Dimensions Theory. Data analysis was taken from four viral tweets collected with the keyword Karen's Diner on Twitter from December 15 to 22, 2022. The study results show that six elements of the Cultural Dimensions Theory are inherent in Indonesian consumers, so they oppose the concept of service presented by Karen's Diner. The element of power distance applies where most Indonesian people have been instilled with the idea that "the buyer is the king", so they do not tolerate the slightest bad action done by the seller. Uncertainty avoidance applies when the Indonesian people protest and urge Karen's Diner Indonesia to make clear written regulations and improve the restaurant's service procedures. The element of masculinity or femininity is represented by netizens who think the restaurant's existence will disappear quickly amid competition in the dynamic Indonesian F&B industry. The Long Term vs Short Term Orientation element applies where the public considers the concept of Karen's Diner Indonesia service intolerable and raises concerns about behavioural deviations in the future. The Indulgence vs Restraint element is represented by people who oppose things that can potentially offend Eastern norms, one of which is product marketing.